Dystrophin gene expression and intracellular calcium changes in the giant freshwater prawn, Macrobrachium rosenbergii , in response to white spot symptom disease infection - Noor, A.F.; Soo, T.C.C.; Ghani, F.M.; Goh, Z.H.; Khoo, L.T.; Bhassu, S. (Elsevier, 2017)
Background Dystrophin, an essential protein functional in the maintenance of muscle structural integrity is known to be responsible for muscle deterioration during white spot syndrome virus (WSSV) infection among prawn species. Previous studies have shown the upregulation of dystrophin protein in Macrobrachium rosenbergii (the giant freshwater prawn) upon white spot syndrome virus (WSSV) infection. The literature has also suggested the important role of calcium ion alterations in causing such muscle diseases. Thus, the interest of this study lies within the linkage between dystrophin functioning, intracellular calcium and white spot syndrome virus (WSSV) infection condition. Methods In this study, the dystrophin gene from M. rosenbergii (MrDys) was first characterised followed by the characterization of dystrophin gene from a closely related shrimp species, Penaeus monodon (PmDys). Dystrophin sequences from different phyla were then used for evolutionary comparison through BLAST analysis, conserved domain analysis and phylogenetic analysis. The changes in mRNA expression levels of dystrophin and the alteration of intracellular calcium concentrations in WSSV infected muscle cells were then studied. Results A 1246 base pair long dystrophin sequence was identified in the giant freshwater prawn, Macrobrachium rosenbergii (MrDys) followed by 1082 base pair long dystrophin sequence in P. monodon (PmDys). Four conserved domains were identified from the thirteen dystrophin sequences compared which were classified into 5 different phyla. From the phylogenetic analysis, aside from PmDys, the characterised MrDys was shown to be most similar to the invertebrate phylum of Nematoda. In addition, an initial down-regulation of dystrophin gene expression followed by eventual up-regulation, together with an increase in intracellular calcium concentration [Ca2+]i were shown upon WSSV experimental infection. Discussion Both the functionality of the dystrophin protein and the intracellular calcium concentration were affected by WSSV infection which resulted in progressive muscle degeneration. An increased understanding of the role of dystrophin-calcium in MrDys and the interactions between these two components is necessary to prevent or reduce occurrences of muscle degeneration caused by WSSV infection, thereby reducing economic losses in the prawn farming industry from such disease.